A Note on the Ancient Name of Dayr al-Barshā - Willems, Harco (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
This article supplements a longer study published in ZÄS 132 (2005), pp. 173-189. It specifically addresses the place name Tjerty mentioned in the inscriptions accompanying the scene showing the colossal statue of the nomarch Djehutihotep, that exists in his tomb in Dayr al-Barshā. It is argued that the name al-îūd, used by the local population of Dayr al-Barshā for an open area in the south of the village, goes back to the ancient name Tjerty, adding an important argument in the discussion over the location of that settlement and the place where the Djehutihotep statue was erected.